Pancasila sebagai Entitas dan Identitas Bangsa Indonesia serta Perwujudan Profil Pelajar Pancasila pada Pendidikan yang Berpihak pada Peserta Didik dalam Pendidikan Abad ke-21 di SMA N 2 Medan - Agustina Aritonang; Liesna Andriany (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Pancasila, as the basis of the Republic of Indonesia, has a very important role in shaping the identity and character of the nation. However, challenges arise in deeply implementing the values ​​of Pancasila, especially among high school students. This study aims to identify challenges in realizing Pancasila as an entity and identity of the Indonesian nation, as well as seeing how the profile of Pancasila students is reflected in 21st century education at SMA N 2 Medan. The research methods used were participant observation, interviews, and document analysis. The results of the study show that understanding and appreciation of Pancasila values ​​among SMA N 2 Medan students is still limited, with the lack of relevance of Pancasila values ​​in the context of students' daily lives being one of the main challenges. This research provides a deeper understanding of the role of Pancasila in 21st century education and provides a basis for developing more effective learning strategies to raise the profile of Pancasila students in the future.